LATE-ONSET PROXIMAL HUMERUS LESION PRESENTING WITH SOLITARY BONE METASTASIS: A DIAGNOSTIC CHALLENGE AFTER 12 YEARS OF REMISSION - Esmez, Omer; Esmez, Merve Yıldız; Deniz, Gülnihal (My University, 2025)
Breast cancer is one of the most common tumors in women. One in eight women may encounter this disease at some point in their lives, and metastasis may develop even after many years of remission. This case report describes a rare humerus metastasis presenting with pain and swelling in the right shoulder in a woman in her 60s who was diagnosed with mixed-type (invasive ductal and lobular) carcinoma of the left breast in early 2012 and who underwent modified radical mastectomy and adjuvant treatments for 12 years of remission. Positron emission tomography imaging revealed a hyper metabolic lesion in the proximal right humerus. Magnetic resonance imaging and biopsy revealed a malignant epithelial tumor indicating metastatic breast cancer. The patient underwent palliative radiotherapy and was started on ribociclib (Valamor) as systemic treatment. However, widespread itching and vitiligo-like skin changes developed on the hands and face due to the treatment. This case emphasizes the importance of long-term clinical and radiological follow-up and the need to be careful about skeletal metastases that may occur in the late period in breast cancer patients.
Keywords: Humerus; Bone neoplasms; breast neoplasms; lobular carcinoma; neoplasm recurrence.